Samarbejdspolitikken og jødernes redning i oktober ’43. Rambams historikerenquete - Indledning - Stræde, Therkel (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
The first scholar to investigate and conclude on the October 1943 rescue of the Jews of Denmark was Israeli historian Leni Yahil. Her doctoral dissertation The Rescue of Danish Jewry (Hebrew 1967) presented the successful rescue of 95 percent of the country’s Jews as a concerted action of the Danish politicians and civil service, the upcoming resistance movement, and – crucially – the grassroots activism of ordinary Danes. While the political and governmental system pursued a policy of cooperation with the Germans mostly named collaboration in international scholarship, and Danish resistance fought the very same policy, both shared with the vast majority of Danes a value system based on (Yahil) “a high level of ethics and the love of freedom and democracy”. This value system – emphasized by Yahil, accepting the master narrative of the 19th century Danish Lutheran minister and liberal politician N.F.S. Grundtvig and his later followers – was rooted in the strong social integration and democratic training characteristic of Danish civil society. Thus, in Yahil’s eyes, the collaboration policy, having protected this civil society and made the Germans postpone their attack on Denmark’s Jews, became one important factor amongst several that together made helping the persecuted Jews possible, and the “natural” choice for ordinary Danes. The article discusses Leni Yahil’s interpretation as well as the ambivalent reactions of Danish historians to her works.